Prevalence of canine ehrlichiosis in Cacoal, Rondônia: A retrospective laboratory study (Research, Society and Development, 2025)
Canine monocytic ehrlichiosis is a tick-borne disease with high prevalence in tropical regions such as Rondônia, where the climate favors the proliferation of these vectors. Caused by the bacterium Ehrlichia canis and primarily transmitted by Rhipicephalus sanguineus, the disease presents variable clinical signs, making diagnosis based solely on observable symptoms difficult.This study aimed to analyze the prevalence of canine ehrlichiosis in Cacoal, Rondônia, between May 2024 and May 2025, considering sex, age, breed of the dogs, and climatic conditions. Data from the VetCare Veterinary Laboratory were evaluated, including complete blood counts, blood smears, and rapid immunochromatographic tests. Results indicated that the disease remains one of the main infections affecting dogs in the region, with variations in clinical signs and patterns related to epidemiological and climatic variables. It is concluded that integrated actions involving prevention, early diagnosis, and proper clinical management are essential to reduce the incidence of ehrlichiosis and minimize its impact on animal health and welfare.